2017
DOI: 10.1161/hypertensionaha.117.09598
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Mineralocorticoid Receptor Mediates Parenchymal Arteriole and Posterior Cerebral Artery Remodeling During Angiotensin II–Induced Hypertension

Abstract: The brain is highly susceptible to injury caused by hypertension because the increased blood pressure causes artery remodeling that can limit cerebral perfusion. Mineralocorticoid receptor antagonism prevents hypertensive cerebral artery remodeling, but the vascular cell types involved have not been defined. In the periphery, the endothelial mineralocorticoid receptor mediates hypertension-induced vascular injury, but cerebral and peripheral arteries are anatomically distinct; thus these findings cannot be ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…Several significant findings were revealed from hypertensive mice. First, consistent with previous studies in various models of hypertension (Chan et al, ; De Silva et al, ; Diaz‐Otero et al, ; Pires et al, ; Sweet et al, ), PA from hypertensive mice show enhanced myogenic tone. Second, both an increase in spontaneous and myogenic‐evoked astrocyte MD Ca 2+ events were observed.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several significant findings were revealed from hypertensive mice. First, consistent with previous studies in various models of hypertension (Chan et al, ; De Silva et al, ; Diaz‐Otero et al, ; Pires et al, ; Sweet et al, ), PA from hypertensive mice show enhanced myogenic tone. Second, both an increase in spontaneous and myogenic‐evoked astrocyte MD Ca 2+ events were observed.…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, we demonstrated that during myogenic (pressure‐evoked) constrictions, astrocytes respond with an increase in Ca 2+ resulting in the release of vasoactive signals which aid in the maintenance of parenchymal arteriole (PA) tone (Kim et al, ). Chronic hypertension causes arteriole remodeling (Baumbach & Heistad, ; Hart, Heistad, & Brody, ; Intengan & Schiffrin, ) and increases in vascular tone (Chan, Sweet, & Cipolla, ; De Silva, Kinzenbaw, Modrick, Reinhardt, & Faraci, ; Diaz‐Otero et al, ; Iddings, Kim, Zhou, Higashimori, & Filosa, ; Pires, Jackson, & Dorrance, ; Sweet, Chan, & Cipolla, ). In addition, chronic hypertension evokes a rightward shift of the CA curve (Paulson, Waldemar, Schmidt, & Strandgaard, ; Saavedra, Benicky, & Zhou, ) protecting the brain from high pressures.…”
Section: Introductionmentioning
confidence: 99%
“…A servo‐null system was used to pressurize the arterioles, and a leak test was performed prior to each experiment. Arterioles were pressurized to 60 mm Hg until the development of stable myogenic tone (% tone = [1−(active lumen diameter/passive lumen diameter)] × 100. The diameter of the arterioles was recorded using MyoView 2.0 software (Danish Myo Technology, Aarhus, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…Blood pressure was measured in conscious rats by tail-cuff plethysmography using a RTBP1001 tail-cuff blood pressure system (Kent Scientific, Torrington, CT) as described previously. 5,21,22…”
Section: Tail-cuff Plethysmographymentioning
confidence: 99%
See 1 more Smart Citation